Integrating sustainable development goals and climate change mitigation targets: Insight from Malaysia - Mustafa, Maizatun; Abu Hanifah, Norha (2019)
The Paris Agreement on Climate Change, and the 2030 Agenda for Sustainable Development were negotiated in parallel and adopted by the world’s leaders in 2015. Through the former, countries worldwide including Malaysia made a climate change commitment based on the nationally determined contributions (NDC) towards a zero-carbon economy. Whereas the Sustainable Development Goals (SDG) which form the centre piece of the 2030 Agenda include SDG 13 on tackling climate change and its impacts. One contentious issue being debated is pertaining to NDC and SDG obligations of the developing countries. Previously, international conventions set binding targets only on the developed nations to reduce their emissions. However, with the new international commitments being ratified, the focus is turning to the developing countries which are currently dominating global carbon emissions. On the part of Malaysia as a developing nation, commitment towards the Paris Agreement and the SDG necessitates actions taken to balance national challenges with the urgent need for climate change mitigation which are complex issues. This paper seeks to understand Malaysia’s trends in adoption of climate strategies within the law, and identify possible policy coherence in the implementation of the NDC and SDG. Taking into consideration the challenge to reconcile policy agendas on economic growth with the need to move away from unsustainable economic practices, this paper examines the way in which Malaysia is mitigating climate change and upholding the SDG which possess fundamentally different problems as compared to that of developed nations. It is contended that through sufficient understanding of coherences between the implementation of the NDC and SDG that strategies within the legal framework can be geared at exploiting the nexus between emission reduction and development priorities so that growth is consistent with climate change objectives of the NDC and SDG.